(3GdCeQ GdeMce GdeQHhW ajeG jdRe Cgd WQjb Gddg JYGdi ef GdTQhWs - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s ((3MGLj Hf EHQGgje Hf Ydj GdJQGHjs)
(3ChdgG (B:s
(3bGd eMj GdOjf eMeO Hf Ydj Hf eMeO GdMGJej GdCfOdSjGdMeO ddg GdPj gOGfG bGd GdOjf GdfUjMI KdGKG bGdhG def jG QShd Gddg bGd(B: (3ddg hdQShdg hdCFeI GdeSdejfs
(3BNQgG (B:s
(3hCYfj HGdMb gfG aj SjQI GdefGRd eG jfRd ef Gddg JYGdi Ydjge ef GddWGFa aj MGd afGge Yf fahSge hYfges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 281s
(3eYLe GdeDdajf(B: 3 / 531s
(3cTa GdXfhf(B: 1 / 168s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs